2022
DOI: 10.37335/ijek.v10i2.174
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Barriers Which Drive Smes in Relation to Corporate Social Responsibility? Literature Review

Abstract: Small and medium-sized enterprises (SMEs) cannot be considered a "shrunken" of large enterprises. They are highly heterogeneous, usually have more informal organizational characteristics, and do not have departments dedicated explicitly to corporate social responsibility (CSR) tasks. Therefore, research on CSR in SMEs faces many challenges. The situation is a complex phenomenon, primarily because the nature of CSR is influenced by the environment uniqueness in which it is studied or practiced. This paper aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The effectiveness of production capacities, problems with the distribution of products/services, or issues with suppliers are attributes of operational risk that are evaluated the worst in Slovak SMEs. Authors Rózsa et al [17] and Małkowska et al [19] share the same opinion, i.e., they state that the evaluation and measurement of SME performance is an important element of prosperous businesses and, therefore, it is necessary to change the thinking of SME owners in the financial area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of production capacities, problems with the distribution of products/services, or issues with suppliers are attributes of operational risk that are evaluated the worst in Slovak SMEs. Authors Rózsa et al [17] and Małkowska et al [19] share the same opinion, i.e., they state that the evaluation and measurement of SME performance is an important element of prosperous businesses and, therefore, it is necessary to change the thinking of SME owners in the financial area.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing demands for sustainability lead to a change in the thinking of SME owners in the financial area [17]. As a result of a German study carried out in medium-sized enterprises, factors were identified that influence measures for the transformation of sustainable enterprises [7,18] -1.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Given the importance of financial management in the management of SMEs, the proven positive impact of CSR practices and the perception of sustainability on the financial management of SMEs, the related context including the need for innovation supported by CSR practices, there is a need to look for ways to support these factories and to remove the main barriers to their implementation, of which the much discussed limited access to finance (Rozsa et al, 2022;Baumann-Pauly et al, 2013; of business ventures, including innovative ones, clearly emerges as the most critical.…”
Section: Discussionmentioning
confidence: 99%
“…In today's fast-paced and demanding work environment, employees often find themselves grappling with the challenge of managing their tasks effectively. Heightened risk of job loss, substantial alterations in work roles and responsibilities, the need to acquire new skills, and shifts in management practices frequently result in reduced work performance sustainability (Rózsa et al, 2022a). This also happens in small and medium-sized enterprises (SMEs), which are recognised as comprising approximately 90% of businesses worldwide (Azman & Abdul Majid, 2023), (Šimberová et al, 2022) and employing roughly half of the global workforce.…”
Section: Introductionmentioning
confidence: 99%